2008
DOI: 10.1016/j.molbiopara.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A determination of the steady state lysosomal pH of bloodstream stage African trypanosomes

Abstract: The lysosomal/endosomal system of African trypanosomes is developmentally regulated and is important in the pathogenesis associated with infection of the mammalian bloodstream. Long considered to be a target for drug development, the internal pH of the lysosome has been variously reported to range from <5.0 to >6.0. We have refined a flow cytometric technique using a pH-sensitive probe that specifically targets the lysosome, tomato lectin:Oregon Green 488 conjugate. The probe is delivered to the lysosome with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…This observation, together with the disappearance of individual AMT1;3 spots from the plasma membrane (Movie S3), suggests that at high-ammonium stress, AMT1;3 protein clusters are rapidly internalized. To investigate whether ammonium exerts a specific effect on AMT1;3 localization, we analyzed the cytoplasmic pH of root cells using the Oregon Green 488 fluorescent probe (20) and found that there was no significant difference in cytoplasmic pH in root cells between N-sufficient and high-ammonium conditions (Fig. S4 A-C; P > 0.05), indicating that the effects of ammonium on the localization and dynamics of AMT1:3 proteins are specific to the ammonium ion rather than a result of its action as a weak base.…”
Section: Resultsmentioning
confidence: 99%
“…This observation, together with the disappearance of individual AMT1;3 spots from the plasma membrane (Movie S3), suggests that at high-ammonium stress, AMT1;3 protein clusters are rapidly internalized. To investigate whether ammonium exerts a specific effect on AMT1;3 localization, we analyzed the cytoplasmic pH of root cells using the Oregon Green 488 fluorescent probe (20) and found that there was no significant difference in cytoplasmic pH in root cells between N-sufficient and high-ammonium conditions (Fig. S4 A-C; P > 0.05), indicating that the effects of ammonium on the localization and dynamics of AMT1:3 proteins are specific to the ammonium ion rather than a result of its action as a weak base.…”
Section: Resultsmentioning
confidence: 99%
“…7D). FITC fluorescence is pH sensitive and is rapidly quenched as the probe is internalized into acidified endosomes and delivered to lysosomes (39), which in trypanosomes have an internal pH of ϳ4.8 (33). When normalized to the initial signal, cell-associated fluorescence decayed with essentially identical kinetics and to the same endpoint in control and silenced cells, consistent with equivalent internalization and delivery to the lysosome.…”
mentioning
confidence: 77%
“…Because of this dynamic metabolism, PF parasites can grow normally in the near absence of glucose. However, complete elimination of nutrients by incubation in PBS triggers association of glycosomes with the acidic (pH 4.8 (20)) lysosomal compartment in PF cells, a process similar to pexophagy in yeast (10).…”
Section: Starvation Alters Cellular Ph and Glycosome-resident Proteinmentioning
confidence: 99%